The Enforcement of International Arbitration Award in Indonesia : a Comparative Study with United States, Netherlands and Singapore - Panusun Harahap (Universitas Airlangga, 2019)
An international arbitration award handed down in a territory of a given country may be applied for in another territory, provided that it is a party to the 1958 New York Convention on the Recognition and Enforcement of Foreign Arbitral Award and between those countries there are bilateral or multilateral agreements on the recognition and execution of international arbitration award. An arbitral award, as well as a judge’s decision, may actually be voluntary by the loser or debtor. If the award has been executed in good faith by the losing party, or in other words, his accomplishments have been met with good faith, then the problem is solved. It is not uncommon, however, that although the award is already in place, the losing party does not want to execute the award voluntarily. In this case the winning party or the creditor may submit an application to the Chairman of the Central Jakarta District Court for the international arbitration award to be executed by force (execution forced). In this article, the author will focus on exploring issues in the implementation of international arbitration decisions in Indonesia and looking at implementing foreign arbitral awards in the United States, the Netherlands, and Singapore. The author of the normative juridical research method is carried out by focusing on legal interpretation and legal construction so that it can answer the above problems in depth.